PAVING THE WAY TOWARD FACULTY CAREERS IN HIGHER EDUCATION: STUDENT MENTORING RELATIONSHIP EXPERIENCES WHILE COMPLETING DOCTORAL DEGREES ONLINE - Norina Columbaro; Catherine A Hansman (Adult Education Research Conference, 2016)
The purpose of this study was to explore the existence and nature of mentoring relationships within online doctoral degree programs. Further, it sought to determine how these relationships prepared online doctoral degree graduates for full-time, tenure-track employment in four-year, land-based higher education institutions.
Keywords: online; doctoral degrees; mentoring; faculty